Complete Maxillary Denture Mobility Related to Posterior Tooth Position - Nakakita, Yoshinobu; Ohta, Naoki; Mizuno, Kentarou; Kakihara, Kensuke; Kawasaki, Takao; Notani, Kenji (Nihon Hotetsu Shika Gakkai Zasshi, 1998)
Although a lot of artificial posterior tooth positioning techniques have been proposed, correlation between complete denture stability and posterior tooth position during mastication has not yet been clarified. This study was conducted to analyze the behavior of complete maxillary dentures that have two posterior tooth positions by the simulation method. Three-dimensional mobility of these dentures was measured during biting two sizes of simulated foods on centric and eccentric positions. One of two artificial posterior teeth arrangements was based on the alveolar crest (A-denture) and the other was in a neutral zone of muscular activity (N-denture). The results were as follows: 1. The working side point of two complete maxillary dentures moved downward, forward, and outward when they were loaded on one side. 2. The mobility of complete maxillary dentures was changed by posterior tooth position, simulated food size, mandibular position, and tooth contact on the balancing side. 3. When biting thick food, there was no tooth contact on the balancing side. In this condition, the mobility of A-denture was less than that of N-denture. 4. When biting thin food, there was tooth contact on the balancing side. This contact limited the mobility of two dentures. In this condition, however, the mobility of N-denture was less than that of A-denture.